FEATURES OF COVID-19-ASSOCIATED PNEUMONIA IN UNVACCINATED PATIENTS WITH ARTERIAL HYPERTENSION - Skakun, O. Z. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
Coronavirus disease 2019(COVID-19) is an important medical and social problem. Comorbidities may aggravate the clinical course of COVID-19 and increase mortality. The aimof this study was to investigate the clinical course of the COVID-19 in patients withstages IІ and III hypertension. 135 unvaccinated patients hospitalized for the COVID-19complicated by pneumonia were examined. The patients included in the study were divided into 2 groups: the main group (106 patients with hypertension) and the control group (29 patients without hypertension). In the main group, 11.3% of patients died, and in the control group, 6.9% of patients died. The mean age of the dead patients of both groups was higher than the mean age of the survivors (p = 0.035). It was found that patients with diabetes mellitus had a higher mortality rate than patients who did not have diabetes mellitus (RR= 2.96 [1.01–8.67], p = 0.047). Also, in the main group, the body mass index in patients who died was higher than in survivors (p = 0.02). Creatinine level at the time of discharge was higher in the main group (97.8 ± 4.0 μmol/L) than in the control group (84.2 ± 6.2 μmol/L) (p = 0.008). So, the lethality rate due to COVID-19 complicated by pneumonia in unvaccinated inpatients was 10.4%. Increased body mass index, diabetes mellitus, and old age are risk factors for death from the COVID-19 complicated by pneumonia.